Auswirkungen der Rettungsprogramme auf die Wettbewerbsfähigkeit der Programmländer Portugal und Irland. Endbericht - Lars P. Feld; Patrick F. Hirsch; Ekkehard A. Köhler; Julia Wolfinger; Roland Döhrn; Angela Fuest; Martin Micheli (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
During the Euro-Crisis Ireland as well as Portugal lost access to the capital markets. Both countries sought for financial assistance granted by European institutions, the IMF, and bilateral credit agreements. The funds were disbursed conditional on implementing structural reforms. These reforms were agreed upon by conjoint consent and finally settled in a Memorandum of Understanding (MoU). The key objective of these reforms aimed at regaining competitiveness. In this report, we analyze whether and to what extent the agreed upon reforms have been implemented. In specific, we analyze, whether the reforms have already influenced competitiveness. Finally, we are interested in the expected impact of the reforms on future economic dynamics. The starting situation has been different in the countries under scrutiny: Ireland experienced a period of high growth, which was partly fueled by low interest rates finally culminating into a real estate and credit bubble. Thus, a large part of the reforms focused on restructuring the financial sector. Portugal in contrast showed a rather slow growth performance over a longer time period. After joining the Euro area, Portugal benefited from lower interest rates as well. However, the improved financial conditions mainly spurred consumption. Capital formation was low since the corporate sector was burdened by highly regulated labor and product markets and an oversized government sector. We find that both countries have successfully implemented most of the agreed upon reforms, even if hesitantly in some cases. Indices of product market regulation improved in both countries. This is mirrored in the product market efficiency sub-index of the Global Competitiveness Indicator as well as in the Indicators of Product Market Regulation of the Organisation for Economic Co-operation and Development (OECD). Furthermore, labor market reforms correlate with an increase of labor market efficiency. Considerable progress was made in restructuring the financial sector. However, if measured in growth, the outcome of the reforms is quite different in the two countries. As of today, Ireland is back on a growth path with the negative output gap closing, if not turning into positive; a major revision of Irish GDP impedes a definite answer. In Portugal, potential growth is still extremely low and the recovery after the crisis is not supported by significant empirical evidence. However, international experience suggests that labor market reforms will stimulate growth, as they reduce structural unemployment. Facilitating dynamics in the corporate sector will pay off in terms of higher investment and an increase and modernization of capital stocks. However, these effects will not be visible in the short run because they require some time to unfold.
Additional information: Endbericht - Forschungsauftrag fe 2/16, Bundesministerium der Finanzen, Referat I A 3.
Keywords: 330